2010
DOI: 10.1111/j.1365-2893.2010.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of cellular immune response against Hepatitis E Virus (HEV)

Abstract: Hepatitis E virus infection (HEV) is a major cause of acute viral hepatitis in the developing world. The immunopathology of HEV infections has not yet been elucidated. The virus is noncytopathic, and therefore, liver injury may be attributed to immune-mediated damage by cytotoxic T cells and natural killer cells. Therefore, we studied the nature of immune cells involved in HEV-induced liver damage using immunohistochemistry in liver biopsies taken from patients with HEV-induced acute liver failure and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 29 publications
4
64
0
Order By: Relevance
“…A study of the T Correlations were estimated by calculating Spearman's rank correlation coefficient. cells invading the liver during the acute phase of infection could confirm the hypothesis of impaired recruitment, since activated CD8 ϩ T cells were found recently in liver biopsy specimens from HEV-infected patients (29).…”
Section: Discussionsupporting
confidence: 55%
“…A study of the T Correlations were estimated by calculating Spearman's rank correlation coefficient. cells invading the liver during the acute phase of infection could confirm the hypothesis of impaired recruitment, since activated CD8 ϩ T cells were found recently in liver biopsy specimens from HEV-infected patients (29).…”
Section: Discussionsupporting
confidence: 55%
“…In a recent report, when post mortem liver biopsies from HEV-ALF patients were evaluated to identify the type of cellular infiltrate, it was seen that activated CD8 CTL (Granzyme +ve, perforin +ve) were markedly higher in liver tissues of such patients than in the liver tissue of healthy control liver (collected intraoperatively during cholecystectomy) and were similar to such infiltrate in HBV-ALF, a known model of Th1 mediated immune injury to liver. 63 Further, CTL epitopes have been documented against both ORF2 and ORF3 of HEV genomes in in-vitro studies. 64 In human studies which include HEV infected pregnant females, a decrease in peripheral CD4 count with increase in CD8 count and altered CD4/ CD8 ratio have been documented.…”
Section: Malnutritionmentioning
confidence: 99%
“…Prabhu et al (2010), more specifically demonstrated the involvement of activated CD8+ T-cells containing granzymes in acute live failure cases of HEV infection. 18 The absence of Treg cells in HEV infected liver tissues suggests that no regulation of immune mediated killing during HEV infection might be associated with severity of the disease. À Foxp3 + T (Effector Treg) cells in acute hepatitis E patients were significantly higher compared to controls and recovered individuals.…”
Section: Pathogenesismentioning
confidence: 99%
“…84 HEV antigens were detected in the hepatocytes of infected patients and experimentally infected animals. 18,85 The presence of negative-strand HEV RNA replicative intermediates in the liver of infected rhesus monkeys constituted the first direct evidence of HEV replication in the liver. 7 There is also evidence of extrahepatic replication of HEV like the biliary epithelial cells in rhesus monkeys.…”
Section: Replication Cyclementioning
confidence: 99%
See 1 more Smart Citation